Performance Analysis of an E-commerce Website Using Distributed Servers (Case Study: Ecommerce Bumdes Sarining Kukuh Winangun) - I Kadek Susila Satwika; I Gede Andika (Information Technology and Science (ITScience), 2024)
Digital transformation has significantly altered our interactions by leveraging the internet for fast global information exchange and collaboration. This shift impacts businesses, individuals, organizations, and governments by increasing the demand for fast, reliable web services. To meet these demands, many organizations are turning to distributed server infrastructures, which help handle large storage needs and avoid performance issues. This research focuses on creating a distributed web server system that uses Round-Robin load balancing to evenly distribute traffic and enhance performance. The Round-Robin algorithm’s simplicity and effectiveness in balancing loads, combined with the advantages of virtualization, such as cost efficiency, improved performance, and better resource management are central to this approach. Virtualization also offers improved scalability, accuracy, and security, further enhancing overall system efficiency and effectiveness in data centers. This research evaluates and contrasts the performance of websites utilizing distributed servers against those using single servers. The findings indicate that websites with distributed servers significantly outperform those with single servers. Specifically, distributed servers offer response times that are 5.8 times faster, achieve 2.2 times more successful responses, and transfer 2.1 times more data than single servers. Additionally, single servers experience a much higher rate of timeouts, with 14.2 times more occurrences compared to distributed servers.